Climate Influences on the Radial Growth of Centrolobium microchaete, a Valuable Timber Species from the Tropical Dry Forests in Bolivia - Lopez Callejas, Lidio (2011)
In this study, we use tree-ring records to determine the climate factors controlling the growth of Centrolobium microchaete, a high-value timber species from the tropical dry Chiquitano forest in Bolivia. We present the first tree-ring chronologies from C. microchaete for Concepci´on and Santa M´onica, Bolivia. Statistical analyses show that the chronologies are of good quality and have a significant common signal between trees. The growth of C. microchaete is strongly influenced by climatic conditions during late spring–early summer. Abundant precipitations concurrent with below-average temperatures during this period of the year favor tree growth. Climate variations in late spring–early summer explain 440 percent of the total variance in C. microchaete tree growth during the interval 1943–2005. Minor differences in tree responses to climate recorded between the two stands may reflect differences in the extent of the dry season and in soil water capacity between sites. Although the chronologies cover the past 180 yr, adding samples from older individuals would permit the extension of these records further back in time. The strong climate dependency of tree growth suggests that predicted future climate changes in the region could have a significant influence on C. microchaete tree growth during the 21st century.